Discriminación étnica en Bolivia: Analizando diferencias regionales y por nivel de calificación - Nuñez, Javier; Villegas, Horacio (Estudios de Economía, 2016)
This paper studies the magnitude and variation of ethnic discrimination accross different schooling and geographical niches of the Bolivian labor market. We find that ethnic wage differentials in the Altiplano region are associated with productivity differentials between the indigenous and non-indigenous population, and not with labor market discrimination. However, ethnic discrimination is significant –and in fact more important– than productivity differentials in the Llanos and Valle regions. In addition, we find that ethnic discrimination is more important than productivity differentials in explaining ethnic wage differentials among university graduates, although productivity differentials are more important than discrimination in explaining ethnic wage differentials among workers of lower schooling. Although discrimination and productivity effects have different importance in explaining ethnic wage differentials across different geographical and schooling niches of the Bolivian labor market, a significant part of the overall ethnic wage gap is associated with differences in human capital endowments between both populations. Accordingly, reducing these human capital gaps should lead to a significant reduction in earnings disparities between the indigenous and non indigenous populations in Bolivia.